Media Digital dan Gerakan Sosial: Analisis Logika Aksi Konektif - Sulaiman, Afif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to analyze how digital media influence the political personalization of content and the coordination of collective action in social movements. This research uses a qualitative approach with case studies of two social movements that use digital media as a means of communication and mobilization, namely the Black Lives Matter Movement in the United States, and the Umbrella Movement in Hong Kong. This research adapts the theoretical framework of Bennett & Segerberg in 2012 on the logic of collective action, which is a logic of collective action based on identity personalization, inclusive discourse, and digital media-based communication networks. The results of this study show that digital media allow social movement participants to express their identities individually and collectively, use adaptable discourses that reach a wide public, and coordinate their actions flexibly and dynamically through open and interactive communication networks. This research provides theoretical and empirical contributions to the study of digital media and social movements, as well as practical implications for social actors who want to use digital media as a tool for social change.